2013
DOI: 10.1007/s10493-013-9697-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of amitraz resistance in Brazilian populations of Rhipicephalus (Boophilus) microplus (Acari: Ixodidae) with larval immersion test

Abstract: Among the ectoparasites of cattle, Rhipicephalus (Boophilus) microplus (Canestrini) (Acari: Ixodidae) remains a major cause of economic losses to livestock. The chemical control with acaricides is still the most efficient method available to control ticks. The aims of this study were to diagnose resistance to amitraz in 16 tick populations from the States of São Paulo (14) and Paraná (2), using the larval immersion technique (LIT), and evaluate the effect of synergists [piperonyl butoxide (PBO), diethyl maleat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…microplus specimens from the states of São Paulo, Ceará, Minas Gerais and on many properties in Mato Grosso do Sul (Tables 2 and 3), with these products exhibiting efficacy ranging from zero to 100% for the three analyzed active ingredients (alpha-cypermethrin, cypermethrin and deltamethrin). These results confirmed the results obtained by Koller et al (2009), Gomes et al (2011) and Mendes et al (2013) in Mato Grosso do Sul and those obtained by Mendes et al (2001Mendes et al ( , 2011 and Pereira (2006) in the state of São Paulo. There are no reports of such resistance in Ceará (HIGA et al, 2015), but it has been reported in other states in the northeastern region of Brazil, including Bahia (CAMPOS & OLIVEIRA, 2005;RAYNAL et al, 2013) and Pernambuco (SILVA et al, 2005).…”
Section: Pyrethroidssupporting
confidence: 92%
“…microplus specimens from the states of São Paulo, Ceará, Minas Gerais and on many properties in Mato Grosso do Sul (Tables 2 and 3), with these products exhibiting efficacy ranging from zero to 100% for the three analyzed active ingredients (alpha-cypermethrin, cypermethrin and deltamethrin). These results confirmed the results obtained by Koller et al (2009), Gomes et al (2011) and Mendes et al (2013) in Mato Grosso do Sul and those obtained by Mendes et al (2001Mendes et al ( , 2011 and Pereira (2006) in the state of São Paulo. There are no reports of such resistance in Ceará (HIGA et al, 2015), but it has been reported in other states in the northeastern region of Brazil, including Bahia (CAMPOS & OLIVEIRA, 2005;RAYNAL et al, 2013) and Pernambuco (SILVA et al, 2005).…”
Section: Pyrethroidssupporting
confidence: 92%
“…Although this assay has not yet been recognized by FAO as a trustworthy method for detecting acaricide resistance in tick populations, it has been used to assess the toxicity of chemicals that act systemically, such as fipronil (CASTRO-JANER et al, 2010) and ivermectin (KLAFKE et al, 2006(KLAFKE et al, , 2012. Recently, it was described as a reliable method for detecting resistance to amitraz (MENDES et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…microplus can be diagnosed using the larval stage in in vitro bioassays: a) larval packet test (LPT), originally described by Stone and Haydock (1962), standardized by FAO (1971) and then modified by Miller et al (2002), with the aim of specifically diagnosing amitraz resistance; b) larval immersion test (LIT), originally described by Shaw (1966), then adapted for microcentrifuge tubes by Sabatini et al (2001) and used successfully for diagnosing resistance to ivermectin (KLAFKE et al 2006(KLAFKE et al , 2012 and fipronil (CASTRO-JANER et al, 2010); and c) syringe immersion test (SIT), described by Souza et al (2008) although not yet standardized for routine use as an acaricide resistance diagnostic tool. Recently, Mendes et al (2013) described the use of LIT for diagnosing amitraz resistance in R. (B.)…”
Section: Introductionmentioning
confidence: 99%
“…However, utilization of acaricides causes drug resistance in ticks, environmental contamination, and meat products with pesticide residues [46]. Vaccine has been considered as an efficient approach to control ticks [7, 8].…”
Section: Introductionmentioning
confidence: 99%